Greater volumes of high-intensity running lead to muscle-tendon injuries in professional Brazilian soccer players - Javier Raya-González; Tomás García-Calvo; David Lobo-Triviño; Ana Rubio-Morales; Rodrigo dos Santos Guimarães; Daniel Castillo (European Journal of Human Movement)
The aim of this study was twofold: i) to compare the workload between injury condition and the control condition in professional Brazilian soccer players, and ii) to analyze the risk of muscle-tendon injury associated with increased weekly workload. Twenty-three muscle-tendon injuries related to 15 professional Brazilian soccer players were considered for this retrospective study. Muscle-tendon injuries were recorded according to the International Olympic Committee (IOC) guidelines, and the weekly accumulated workload was recorded through Global Position System devices. Higher weekly values of total distance (TD, 12.96%), high-intensity running (HIR, 16.06%) and high-speed running (HSR 29.46%) were observed for the injury condition when compared to the control condition. Furthermore, it was found that the risk of suffering a muscle-tendon injury is reduced by 56.77% (RR = 1.44) when the weekly TD is below 26698.6 m, by 45.1% (RR = 1.45) when the weekly HIR is below 3048.3 m, and by 17.86% (RR = 1.82) when the weekly HSR is below 1228.8 m. These results suggest that strength and conditioning coaches should adjust the training running demands based on the values related with an increased injury risk, considering the running demands from matches and avoiding abrupt changes in workload.